Personalized Learning Activities in English for Grade 5 - Anabo, Roy; Gereña, Christie (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to develop Personalized Learning Activities in English for Grade 5 students among the eleven (11) public elemen-tary schools in San Julian District and eight (8) public elementary schools in Sulat District, Division of Eastern Samar, Academic Year 2019-2020. The study utilized a descriptive research method with a survey questionnaire and proficiency test in English for Grade 5. Based on the results the public elementary schools in San Julian Dis-trict and Sulat District, Division of Eastern Samar obtained a mean score that falls under the category “did not meet expectations” where all competencies obtained an overall mean score of 2.415 in-terpreted as “poorly developed”. Results implied that the Grade 5 students did not develop the skills and competencies they needed to improve in English competencies by the Grade 5 students. However, results implied that students have not mastered all the competen-cies in the subject and teachers are not acquainted with personal-ized learning activities as innovative materials in teaching. They relied on the use of textbooks, visual aids, and printed materials to teach English lessons. Teachers teaching English were not acquaint-ed with the use of a personalized learning approach as a new strate-gy in teaching and never be used by the teacher, majority of the iden-tified problems were considered as always problems by the Grade 5 teachers in teaching English. It is highly recommended an interven-tion material for pupils to develop mastery of the least learned com-petencies in English to achieve a higher academic performance level in the subject.